Simple sequence repeat analysis and qualitative pathway analysis of Rathayibacter toxicus - Chumachenko, Kseniya (Kansas State University, 2020)
Rathayibacter toxicus is a plant pathogenic bacterium vectored by Anguina species (nematodes) and hosted by grass species in several genera in the Poaceae family including, Lolium, Lacnagrostis, and Polypogon. Rathayibacter toxicus forms bacterial galls in developing grass ovules where it produces a dangerous neurotoxin, tunicamycin. Grazing animals that consume toxic galls develop convulsions and staggers, often resulting in death. Rathayibacter toxicus is indigenous to Australia, but concern for global spread and potential impact to livestock industries resulted in its designation as a U.S. Select Agent pathogen. Several genetic and genomic studies including MLST, ISSR, and WGS support genetic population groupings and identified a newly emerged population (RT-I) in South Australia. Unique attributes of RT-I preclude determination of its geographic or phylogenetic origin. Simple Sequence Repeats (SSRs) are short tandem nucleotide repeats that vary in size and number of repeats among and within genomes and have been useful in determining evolutionary heritage. Unlike other genome components, SSRs generally have faster mutation rates and have been used as the basis of phylogenetic and phylogeographic analyses in many organisms including bacteria and plants. SSRs in R. toxicus were identified and analyzed to help determine the origin and evolutionary trajectory of the bacterium. Whole genome sequences of 16 strains representing the five previously identified genetic populations of R. toxicus were used for SSR discovery and analysis. Ten SSRs were selected based on common parameters and two were PCR-verified on all available strains for confirmation of the sequence data. Individual SSRs greatly varied across genomes and the results of different combinations of concatenated SSRs generated different phylogenies. Some but not all SSR combinations corresponded to previous studies’ results. SSR analyses were inconclusive and not predictive for phylogeny or geographic origin. To summarize, SSRs may lead to different conclusions depending on which SSRs are included in the analysis and how many SSRs are analyzed. Caution should be applied when using SSR analysis for understanding evolutionary dynamics of R. toxicus. For diagnostic purposes, different SSR markers within R. toxicus had varying levels of specificity, with one SSR being able to differentiate to strain level, some SSRs to population level, and others only to species level, R. toxicus generally. The analyzed SSR markers were all unique to R. toxicus and created a spectrum of diagnostic specificity. Rathayibacter toxicus and its toxin has been a threat to Australian agriculture for decades and now threatens other countries because of the increase in globalized trade markets including hay exports from Australia. Countries including the U.S. may be at risk of R. toxicus introduction, which may include potential establishment, spread, and ultimate disease outbreaks. It is necessary to understand how the pathogen survives and spreads within and from the source country, how it is moved from source to destination country, and how environmental conditions at the destination may facilitate pathogen establishment. This qualitative pathway analysis was developed to study the possible avenues through which R. toxicus may elude containment and reach areas outside of outbreak centers in Australia. A scenario of R. toxicus spread was analyzed which included assuming a range of concentration of bacterial galls within a hay field harvested for hay bales for export out of the country. It is evident that risk exists for R. toxicus gall release at multiple points throughout its journey from a grass panicle in an Australian paddock, all the way through to the arrival on a packaged bale of hay reaching a feeding pasture in a U.S. livestock farm.
Keywords: plant pathology; plant disease; biosecurity; genetics; population genetics; phylogenetics